The Influence of Self-Efficacy on Interest in Participating in the Merdeka Belajar Kampus Merdeka (MBKM) Program - Thahir, Muthahharah; Widiawati, Widiawati; Rachmaniar, Ananda (Indonesian Research Journal in Education |IRJE|, 2024)
The purpose of this research was to ascertain how self-efficacy affected students' desire to enrol in Universitas Ma'soem's MBKM program. 1539 Universitas Ma'soem students from the 2020–2023 academic year made up the population. Moreover, the Krejcie and Morgan table revealed that the sample size was 306 (19.88%). A questionnaire with five responses and a Likert scale model served as the research instrument. All the questionnaire's items are valid, and the questionnaire reliability test yielded calculated self-efficacy R-values of 0.761 and interest R-values of 0.760, which are higher than Cronbach's alpha reliability coefficient of 0.70, indicating the questionnaire's reliability. The SPSS application was utilized.